Implementation of Blended Learning Model Through Wordwall Application in Improving Critical Thinking of Islamic Elementary School Students - Muzaini, M Choirul; Noptario, Noptario; Arifin, Nurul (Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2023)
A less enjoyable teaching and learning process results in a decrease in critical thinking skills and student learning outcomes. The related impact can be resolved through action research which aims to improve the critical thinking skills and learning outcomes of students by utilizing blended learning with word wall application. This study uses a quantitative research approach with a class action research method. The subjects in this study were all grade VI (six) Madrasah Ibtidaiyah students totaling 35 students. The instruments used in this study used observation sheets with the aim of getting news related to teaching and learning activities, rubrics used to measure students' critical thinking skills, and tests with the aim of measuring students' learning outcomes. The data analysis technique used is the percentage technique to see the percentage picture of students, categorical to classify data, and comparative to compare data results. The results of this study obtained several findings including : 1) students' critical thinking increased, with a vulnerable average score of students' critical thinking ability level from Cycle I to Cycle II of 11.35 points; 2) the average student learning outcomes increased, with a score difference from Cycle I to Cycle II of 10.11 points. While the percentage of classical learning completeness increased, with a percentage difference of 22.85%. So based on these results, it can be concluded that the application of the blended learning model on the wordwall application can make learning more fun, so that it has implications for increasing students' critical thinking.